Tuhfah al-Mursalah ila Ruh al-Nabiy as the Source of the Doctrine Seven Grades of Being in the Malay-Indonesian Archipelago - Faudzinaim Badaruddin (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2021)
The ‘doctrine of the seven grades’ or martabat tujuh is a popular Sufi teaching. It originated in early seventeenth-century India and was later introduced in Aceh and gained considerable popularity among the Malay Sufis. Despite its wide acceptance in Sufi circles, martabat tujuh seems incompatible with Islam and its strict belief in a transcendent God. The purpose of this article is to examine the history of the Tuḥfa al-Mursala as the source text of this doctrine and to establish its authenticity as a legitimate source of Sufi thought in Southeast Asia. Based on detailed document analysis, the study found that its original purpose was to correct misconceptions of Ibn ʿArabī’s waḥdat al-wujūd. The text is attributed to Fadlullah al-Burhanpuri, an eminent Sufi scholar living in the seventeenth century. The Tuḥfa al-Mursala and its commentaries are an important source for the study of Sufi thought in the archipelago and the doctrine of martabat tujuh.